FREQUENCY OF RISK FACTORS AMONG PATIENTS WITH DIABETIC FOOT ULCER (DFU): AN INSTITUTIONAL-BASED CROSS-SECTIONAL STUDY - Bashir Ahmed Khuhro1, Nasrullah Aamir2, Zahoor Elahi Soomro3, Jaendo Khan Daidano4 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Objective: To determine the frequency of risk factors involved in development of DFU among adults with diabetes Mellitus. Study Design: Cross-sectional study Place and Duration or study: People’s University or Medical & Health Sciences for women 1st February 2018 to 31st January 2019. Materials & Methods: A total of 163 consecutive patients with diabetic foot ulcer were recniited. The risk factors e.g. age, gender etc. were identified by detailed history, physical and local examination of foot and necessary investigations. The appropriate treatment was given to all patients with DFU. Data were collected on a special proforma for ‹analysis. Results: Out of 163 patients 68.79c were male. Majority (39.99r) o1 patients was in the range of 61-70 years and 84% of participants had poorly controlled diabetes. Ninety-eight (60.1%) were smokers. Neuropathy was present in 47.229c patients, 28.29c were with neuroischemic and 24.5 patients have vasculopathy. Foot deformities were also common risk factor and present in 63.29c. The trauma was major external factor noted in 65% patients with DFU. Previous history of ulcer and amputation was noted as 8.69a and 6.79c respectively. Direct relation was found between the neuropathy and trauma. Conclusion: this study supports that etiology of DFU is multifactorial. The peripheral neuropathy, vasculopathy, uncontrolled diabetes and trauma are most significant risk factors involved in development of DFU. Therefore, education and awareness program for awareness of these risk factors may decrease the prevalence of DFU.